Evaluation of Patient Safety Status in Teaching Hospitals of Arak City - Mohanna Rajabi (Patient Safety and Quality Improvement Journal, 2023)
Introduction: Patient safety and quality of care are among the most important points that hospitals should emphasize. Therefore, this study was conducted to evaluate the status of mandatory patient safety standards in teaching hospitals in Arak City. Materials and Methods: This cross-sectional descriptive study was conducted from February to July 2023. The data collection tool was a checklist of mandatory standards from the Patient Safety Friendly Hospital Initiative (PSFHI). The required data were gathered by reviewing the documents, interviews, and observations in five teaching hospitals in Arak City. Data were analyzed using SPSS software and descriptive statistical methods. Based on the average compliance score, these hospitals were classified as weak (lower than 50%), moderate (50-70%), and good (higher than 70%). Results: These hospitals’ average compliance with mandatory patient safety standards was 89.48±4.82, indicating good compliance. The average compliance in the areas of leadership and management, patient and public involvement, safe and evidence-based clinical practices, and safe environment in teaching hospitals of Arak City, with a score of 93.28±2.5, 80±20.9, 84.65±6.14 and 100, respectively, are in good status. Conclusion: Five teaching hospitals in Arak City comply well with mandatory patient safety standards. However, since achieving 100% compliance with the mandatory standards is necessary to obtain the title of Patient Safety Friendly Hospital, and none of the studied hospitals have acquired the necessary score to achieve this title, more effective managerial efforts s are crucial to full compliance with mandatory standards.